2015
DOI: 10.1016/j.cplett.2015.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible temperature quenching and antiquenching of photoluminescence of ZnS/CdS:Mn/ZnS quantum well quantum dots

Abstract: An experimental observation on irreversible thermal quenching and antiquenching behavior is reported for photoluminescence (PL) of ZnS/CdS:Mn/ZnS quantum well quantum dots (QWQDs) prepared with a reverse micelle method. The dual-color emissions, a blue emission band centered at 430 nm and a Mn 2+ 4 T 1 → 6 A 1 orange emission peak at 600 nm, were found to have different dependences of emission intensity on temperature in the range of 8-290 K. Depending on Mn 2+ doping concentration, they can both show strong a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Here are some examples on the emission color, work temperature, and emission intensity as compared to their room-temperature intensity for typical highly efficient nitrides phosphors: AlN:Eu 2+ (blue, 240 °C, ∼50%), Sr 2 Si 5 N 8 :Eu 2+ (red, 150 °C, ∼86%), Ca-α-sialon (yellow, 230 °C, ∼60%), and β-sialon (green, 150 °C, ∼90%) . At higher temperature, some peculiar photoemission phenomena which always do not appear at room or lower temperature may show up along luminescence quenching processes, for example, (i) monotonic blue shift of photoemission in α-sialon:Yb 2+ , BaAl 2 Si 2 O 8 :Eu 2+ , CaWO 4 :Bi, and CaMoO 4 :Bi; (ii) coexistence of blue-shift and red-shift of Eu 2+ emission in Sr 2 Si 5 N 8 :Eu 2+ ; (iii) shift of multiple emissions toward different directions in ZnO; (iv) anomalous initial photoemission enhancement followed by subsequent quenching in colloidal quantum dots, LuVO 4 :Bi and KZnF 3 :Mn; (v) reversible or irreversible luminescence degradation in X2-Y 2 SiO 5 :Eu,Bi 1 or ZnS/CdS:Mn/ZnS, respectively; (vi) broadening line width of photoemission in YAG:Ce and Sr 8 (Si 4 O 12 )­Cl 8 :Eu 2+ ; and (vii) temperature-dependent energy transfer from one dopant to another in Na 2 SrMg­(PO 4 ) 2 :Eu 2+ ,Mn 2+ or from host to dopant in ScVO 4 :Bi, and so forth. Moreover, tunable emission colors can be achieved easily by controls over photoemission shift or relative intensity ratio of multiple emission bands.…”
Section: Introductionmentioning
confidence: 99%
“…Here are some examples on the emission color, work temperature, and emission intensity as compared to their room-temperature intensity for typical highly efficient nitrides phosphors: AlN:Eu 2+ (blue, 240 °C, ∼50%), Sr 2 Si 5 N 8 :Eu 2+ (red, 150 °C, ∼86%), Ca-α-sialon (yellow, 230 °C, ∼60%), and β-sialon (green, 150 °C, ∼90%) . At higher temperature, some peculiar photoemission phenomena which always do not appear at room or lower temperature may show up along luminescence quenching processes, for example, (i) monotonic blue shift of photoemission in α-sialon:Yb 2+ , BaAl 2 Si 2 O 8 :Eu 2+ , CaWO 4 :Bi, and CaMoO 4 :Bi; (ii) coexistence of blue-shift and red-shift of Eu 2+ emission in Sr 2 Si 5 N 8 :Eu 2+ ; (iii) shift of multiple emissions toward different directions in ZnO; (iv) anomalous initial photoemission enhancement followed by subsequent quenching in colloidal quantum dots, LuVO 4 :Bi and KZnF 3 :Mn; (v) reversible or irreversible luminescence degradation in X2-Y 2 SiO 5 :Eu,Bi 1 or ZnS/CdS:Mn/ZnS, respectively; (vi) broadening line width of photoemission in YAG:Ce and Sr 8 (Si 4 O 12 )­Cl 8 :Eu 2+ ; and (vii) temperature-dependent energy transfer from one dopant to another in Na 2 SrMg­(PO 4 ) 2 :Eu 2+ ,Mn 2+ or from host to dopant in ScVO 4 :Bi, and so forth. Moreover, tunable emission colors can be achieved easily by controls over photoemission shift or relative intensity ratio of multiple emission bands.…”
Section: Introductionmentioning
confidence: 99%
“…5(a). The phenomenon of luminescence intensity increase with temperature rise is called negative thermal quenching (NTQ) [33, 34 and references therein], anomalous thermal quenching [35] or antiquenching [36]; the notion of critical temperature is introduced by Rechnikov [33]. It was observed that in the studied Cu2O single crystals value of critical temperature T0 varies in the 20-55 K limits depending on the sample, particular emission band and excitation light power.…”
Section: Sample Sc(111)mentioning
confidence: 99%
“…Previously NTQ of emission bands was observed in different materials and explained by different mechanisms: in doped GaN -by quenching of a competitive intense luminescence band or a nonradiative channel [34], in sandwiched single layer MoS2 -by raising radiative recombination rate of the excess delocalized carriers created from the carrier hopping from the shallow defect states to the band edges [35], in CdMnTe -by participation of intermediate states of impurities in recombination processes, in ZnO and CdMnTe -by presence of intermediate defect states and nonradiative channels [41][42]. Some authors explain NTQ by thermal activation of charge carriers and trapped excitons from shallow traps followed by their localization at radiative centers [31,36,43].…”
Section: Single Crystalsmentioning
confidence: 99%
“…Since the number of charge traps may depend on the previous thermal and irradiation history, the resulting PL signals could be irreversible with temperature, 32 even leading to irreversible temperature antiquenching, as observed in some core-shell quantum dots. 33 We hence consider that the irreversible temperature antiquenching behavior observed in this work can also be interpreted in terms of the thermally activated trapping/ detrapping processes associated with certain deep traps. A schematic representation of the energy levels for the ground and excited states of the twofold-coordinated Si and the related deep trap states is shown in Fig.…”
mentioning
confidence: 95%